Genome-wide Identification And Functional Characterisation Of Β-1,3-glucanase Genes During Biotic And Abiotic Stresses In Hevea Brasiliensis - Lui, Xin Jie (2024)
Natural rubber (NR) is one of the most widely used industrial raw materials while Hevea brasiliensis is the most exclusive species to produce high-quality NR commercially. However, the cultivation of H. brasiliensis faces numerous challenges which can negatively impact the production of natural rubber, such as the specific growth environment requirement of H. brasiliensis and its high susceptibility to fungal infections. Hence, the studies on disease-resistance related genes as well as breeding new disease-resistant varieties are crucial to maintain the role of H. brasiliensis as the promising source of natural rubber. β-1,3-glucanases (GLUs) are pathogenesis-related proteins that belong to the family of PR-2 proteins and can be abundantly found in H. brasiliensis. Besides their significance in physiological and developmental processes, they are vital in defending against microbial pathogen invasion with direct fungicidal effects. A few nucleotide sequences encoding GLUs have been identified from H. brasiliensis with their overexpression in response to a few fungal pathogens. However, the main challenges for utilising GLUs in the crop improvement include the lack of curated and characterised GLU gene sequences and understanding regarding the respective gene expression under different physiological conditions. In the current study, GLU sequences deposited in various databases were obtained, manually curated, analysed the gene features and the gene expression analysis under various conditions: different stages of leaves, abiotic and biotic stress.